Adjustment of the structural and functional properties of okara protein by acid precipitation. (October 2020) - Cai, Yongjian; Huang, Lihua; Tao, Xia; Su, Jiaqi; Chen, Bifen; Zhao, Mouming; Zhao, Qiangzhong; Van der Meeren, Paul
Abstract: Acid precipitation has a great influence on the extraction and structural properties of plant proteins, especially for proteins in poorly soluble raw materials. The structural and functional properties of okara protein (OP) precipitated by different acids (HCl, citric acid, and malic acid) were investigated. HCl induced the lowest surface hydrophobicity (H0 ), while citric acid led to the lowest absolute value of ζ-potential and the largest size of OP. By contrast, the highest H0 and absolute value of ζ-potential, as well as the smallest size, were observed in OP precipitated by malic acid. Basic 7S globulin (Bg 7S) was detected in OP, especially for OP precipitated by malic acid and citric acid. Differences were also observed in the functional properties of OP. HCl contributed to the highest solubility, water holding capacity (WHC), foaming ability index (FAI), and foaming stability index (FSI). Citric acid induced the highest oil holding capacity (OHC) and emulsifying stability index (ESI). Malic acid resulted in the lowest FAI, FSI, and ESI. These results indicated that acid precipitation was able to alter functional properties of okara protein via affecting the structure, which made it be appliable in extracting protein from poorly soluble raw materials and widen the applications of obtained protein. Graphical abstract: Image 1